To find the solution, first distribute the coefficients of the parentheses on both sides of the equation:
4x + 3x - 6 = 8x - 6 - x
Combine like terms:
7x - 6 = 7x - 6
Notice that the variable terms and the constants on both sides are the same. Therefore, every value of x will satisfy the equation, resulting in infinite solutions. Thus, the answer is:
infinite solutions.
What is the solution to the equation below?
4x+3(x−2)=8x−(6+x)
This problem requires you to show your work.
(1 point)
Responses
x=6
x is equal to 6
x=−4
x is equal to negative 4
no solution
no solution
infinite solutions
infinite solutions
1 answer